Learning about Chemiosmosis and ATP Synthesis with Animations Outside of the Classroom - Eric E. Goff (American Society for Microbiology, 2017)
Many undergraduate biology courses have begun to implement instructional strategies aimed at increasing student interaction with course material outside of the classroom. Two examples of such practices are introducing students to concepts as preparation prior to instruction, and as conceptual reinforcement after the instructional period. Using a three-group design, we investigate the impact of an animation developed as part of the Virtual Cell Animation Collection on the topic of concentration gradients and their role in the actions of ATP synthase as a means of pre-class preparation or post-class reinforcement compared with a no-intervention control group. Results from seven sections of introductory biology (n = 732) randomized to treatments over two semesters show that students who viewed animation as preparation (d = 0.44, p < 0.001) or as reinforcement (d = 0.53, p < 0.001) both outperformed students in the control group on a follow-up assessment. Direct comparison of the preparation and reinforcement treatments shows no significant difference in student outcomes between the two treatment groups (p = 0.87). Results suggest that while student interaction with animations on the topic of concentration gradients outside of the classroom may lead to greater learning outcomes than the control group, in the traditional lecture-based course the timing of such interactions may not be as important.